2000
DOI: 10.1126/science.288.5469.1215
|View full text |Cite
|
Sign up to set email alerts
|

Rocks from the Mantle Transition Zone: Majorite-Bearing Xenoliths from Malaita, Southwest Pacific

Abstract: Rocks containing high-pressure mineral assemblages derived from the mantle transition zone between depths of about 400 and 670 kilometers occur as xenoliths and megacrysts on the island of Malaita in the southwest Pacific on the Ontong Java Plateau. Observed ultrahigh pressure mineral chemistries include majorite, calcium- and magnesium-perovskite, aluminous silicate phases, and microdiamond. Based on an empirical barometer, majoritic garnets in these xenoliths record pressures of up to 22 gigapascal. The occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 55 publications
0
56
0
5
Order By: Relevance
“…Similar plume head structures have been identi¢ed in place beneath £ood basalt provinces in South America and India, although the OJP, emplaced into an oceanic plate, is unique in that it did not intrude into deep continental roots that explain the far-traveled nature of the Paranä and Deccan remnant structures. The similar seismically slow thick anomalies of all three hotspot plume heads imply that chemical di¡erentiation at the core^mantle boundary, presumably the source of these mantle plumes, is strong and results in long-lived compositional anomalies [48]. Resultant buoyancy of these structures may indicate that plume head remnants ultimately accrete to continental masses and represent a signi¢cant component of continental growth, increasing the overall volume of tectosphere [49].…”
Section: Discussionmentioning
confidence: 90%
“…Similar plume head structures have been identi¢ed in place beneath £ood basalt provinces in South America and India, although the OJP, emplaced into an oceanic plate, is unique in that it did not intrude into deep continental roots that explain the far-traveled nature of the Paranä and Deccan remnant structures. The similar seismically slow thick anomalies of all three hotspot plume heads imply that chemical di¡erentiation at the core^mantle boundary, presumably the source of these mantle plumes, is strong and results in long-lived compositional anomalies [48]. Resultant buoyancy of these structures may indicate that plume head remnants ultimately accrete to continental masses and represent a signi¢cant component of continental growth, increasing the overall volume of tectosphere [49].…”
Section: Discussionmentioning
confidence: 90%
“…Из предыдущего раздела видно, что некоторые включения в алмазах и некоторые мантийные ксе-нолиты содержат в себе минералы переходной зо-ны мантии [Collerson et al, 2000;Hayman et al, 2005;Brenker et al, 2007;Wirth et al, 2007] (рис. 6).…”
Section: переходная зона и глубокие горизонты верхней мантииunclassified
“…Несмотря на то, что обнаружение мажорита в ксе-нолитах из альноитов о-ва Малайта [Collerson et al, 2000] было поставлено под сомнение [Neal et al, 2001], в других случаях идентификация минералов переходной зоны не подвергалась критике. Таким образом, вещество переходной зоны может участ-вовать в вулканических процессах, по крайней мере при формировании щелочных магм.…”
Section: переходная зона и глубокие горизонты верхней мантииunclassified
See 1 more Smart Citation
“…However, the relationship between the diverse nature of the Malaitan xenoliths and the unusual generation of the OJP was not examined extensively and remained ambiguous before our studies (Ishikawa et al, 2004) . During our visit to the Solomon Islands in 2000-2001, Collerson et al (2000) reported occurrences of diamond and ultrahigh pressure minerals, such as majorite and silicate perovskite in Malaita alnöites, but no actual mineralogical data. A criticism of the article was published by Neal et al (2001) , which is consistent with my own observations.…”
Section: Historical Background Of Malaitan Xenolithsmentioning
confidence: 99%